Combined endovascular coiling and intra-aneurysmal allogeneic mesenchymal stromal cell therapy for intracranial aneurysms in a rabbit model: a proof-of-concept study. (7th July 2016) - Adibi, Amin; Eesa, Muneer; Wong, John H; Sen, Arindom; Mitha, Alim P
Abstract : Objective: To assess the feasibility and efficacy of clinically translatable adjuvant mesenchymal stem/stromal cells (MSCs) therapy in improving the healing of coiled aneurysms in a rabbit elastase aneurysm model. Methods: Bone marrow-derived MSC populations were isolated from three rabbit donors in a serum-free environment and independently characterized to confirm their identity. Elastase-induced carotid aneurysms were created in nine New Zealand white rabbits. Each animal received one of the following treatments based on previous randomization: (1) coiling alone (control group); (2) coiling with an intra-aneurysmal injection of saline (vehicle group); and (3) coiling with an intra-aneurysmal injection of 5 million allogeneic MSCs (treatment group). The animals were followed for 4 weeks post-treatment, at the end of which blinded analyses of angiograms and histology were performed. Results: Histological results in the treatment group showed improvements over the control and vehicle groups, although the improvement over the vehicle group was not significant. Intra-aneurysmal cell therapy with 5 million allogeneic MSCs did not result in any major adverse events. Angiographic results did not show any significant difference among groups. Conclusions: This proof-of-concept study shows that adjuvant MSC therapy for intracranial aneurysms is feasible and may enhance histological improvement of coiled aneurysms at 4 weeks post-treatment.